Implementasi Sistem Informasi Layanan Kepegawaian di Kantor Pos Ciwastra Menggunakan Metode SDLC (Software Development Life Cycle) - Hermawan, Agus; Najiyah, Ina (Universitas Batanghari Jambi, 2025)
This research aims to design and build an integrated operational information system on a web-based platform as an effective solution to these problems. The system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model, encompassing requirements analysis, UML- based design, implementation with PHP and the Laravel framework, and testing via the black-box method. The result of this research is a functional web-based application that successfully integrates three main modules: operational service logging, employee attendance management, and automated financial reporting. Black-box testing results show that 100% of the system's functionalities are valid and align with defined requirements. The developed system is proven to increase process efficiency, ensure data accuracy, and accelerate report delivery, thereby supporting better decision-making at the Ciwastra Post Office.